Acute oral erythematous candidosis - Ito, Cristiane Yumi Koga [UNESP]; Sangalli, Jorgiana [UNESP]; Pereira, Daniel Freitas Alves [UNESP] (Springer Nature, 2015)
Acute erythematous candidiasis (EC) is cited as the most frequent clinical manifestation among AIDS patients, after pseudomembranous form. Among HIV-positive patients, it was reported as the most commonly observed oromucosal lesion. Higher prevalence of this condition was observed in patients with CD4/CD8 ratio <0.30 and CD4 levels ≤ 200 cells/ mm. Based on these evidences, the presence of EC has been suggested as a marker to diagnose the immune status of HIV-infected individuals.